Perilaku Pasien terhadap Upaya Pembersihan Karang Gigi Di Balai Pengobatan Gigi Puskesmas II Denpasar Timur Kota Denpasar - Arini, Ni Wayan; Pietojo, Harbandinah; Widagdo, Laksmono (Jurnal Promosi Kesehatan Indonesia, 2011)
Periodontal disease is the second largest illness suffered by the community in Indonesia (73.50%), one of its etiologies is tartar which is found in 46.2% of the population. The impact of periodontal disease on systemic health include cardiovascular disease, atherosclerosis, premature birth and low birth weight. The aim of this study is to analyze the factors related to patient’s tartar cleaning behavior on BPG Primary Health Center II, East Denpasar City. This study uses quantitative methods with survey design and cross sectional approaches. Sample size is 185 people. Results showed the majority (70.3%) of respondents did the less practice. Factors which connected to cleaning the tartar formation practice is less support of medical worker (68,1%), and (48,6%) of respondent have middle educational level and the most dominant factor which affect to cleaning tartar practice is medical worker. Variables that are not associated with patient practice of tartar cleaning are age, sex, income, experience of toothache, knowledge, attitudes.